Influence of Temperature on the Thyroidogenic Effects of Diuron and Its Metabolite 3,4-DCA in Tadpoles of the American Bullfrog (Lithobates catesbeianus) - Freitas, Juliane S. [UNESP]; Kupsco, Allison; Diamante, Graciel; Felicio, Andreia A. [UNESP]; Almeida, Eduardo A.; Schlenk, Daniel (Amer Chemical Soc, 2016)
Temperature is a key variable affecting the timing of amphibian metamorphosis from tadpoles to tetrapods, through the production and subsequent function of thyroid hormones (TH). Thyroid function can be impaired by environmental contaminants as well as temperature. Tadpoles can experience large temperature fluctuations in their habitats and many species are distributed in areas that may be impacted by agriculture. Diuron is a widely used herbicide detected in freshwater ecosystems and may impact endocrine function in aquatic organisms. We evaluated the influence of temperature (28 and 34 degrees C) on the action of diuron and its metabolite 3,4-dichloroaniline (3,4-DCA) on thyroid function and metamorphosis in tadpoles of Lithobates catesbeianus. Exposure to both compounds induced more pronounced changes in gene expression and plasma 3,3',5-triiodothyronine (T-3) concentrations in tadpoles treated at higher temperature. T-3 concentrations were increased in tadpoles exposed to 200 ng/L of diuron at 34 degrees C and an acceleration of metamorphosis was observed for the same group. Transcriptomic responses included alteration of thyroid hormone induced bZip protein (thibz), deiodinases (dio2, dio3), thyroid receptors (tr alpha, tr beta) and Kruppel-like factor 9 (klf9), suggesting regulation by temperature on TH-gene expression. These results suggest that environmental temperature should be considered in risk assessments of environmental contaminants for amphibian species.